Our Treatment Strategy for Critical Limb Ischemia. (10th December 2013) - Yamada, Tetsuo; Onishi, Kiyoshi; Utsunomiya, Makoto; Nakamura, Masato
Abstract : For the treatment of critical limb ischemia, collaboration with wound specialists and cardiologists performing revascularization is important. The foot care unit affiliated with related departments opened at our hospital in July 2010 for limb salvage, mainly under the leadership of the departments of cardiovascular internal medicine 　 and plastic surgery. We have treated 194 patients up until October 2012. The primary diseases included 81 cases (87 limbs) of foot ulcer and gangrene, with complications of peripheral arterial diseases (PADs) in all cases. Intravascular treatment was conducted for 69 limbs with PAD complications, and the initial success rate was 85.5%, of which surgical debridement or minor amputation was performed on 32 limbs. Regarding open wounds following operation and chronic ulcer, platelet-rich plasma therapy was conducted in 29 limbs and negative pressure wound therapy in 15 limbs. Among all of the patients treated, 58 limbs healed, 10 cases died, and the others are currently receiving ongoing treatment. Cardiovascular internal medicine specialists and plastic surgeons examine patients together at the outpatient clinic and prepare and implement a multidisciplinary treatment plan including vascular reconstructions and operation. We cooperate with physicians in each related department and efforts in team medicine have been made for the purpose of limb salvage.